Exploring user editing preferences in electronic forms: an empirical study - Marius Breitmayer; Lisa Arnold; Michael Winter; Manfred Reichert (Information Systems and e-Business Management, 2024)
Abstract Electronic forms, such as order entry or tax declarations, frequently serve as the primary point of contact between users and information systems. Given their significance, it's crucial that these forms are intuitive and not burdensome for users to complete. One key aspect influencing the intuitiveness of forms is the sequence in which individual fields must be filled. This article reports on an empirical study involving 162 participants, which explored the intuitiveness of user forms across diverse scenarios. The study had two main objectives. Firstly, it sought to understand how users perceive different sequences of form fields in terms of intuitiveness. Secondly, it investigated the possibility of an intuitive sequence for form fields. The study found significant differences in intuitiveness among various ways of organizing form field sequences. Furthermore, it revealed a common understanding among users about the (sub-)sequence in which form fields should be arranged, notably that fields requiring file uploads should be located at the end of the form. The findings of this study provide valuable insights for developing more intuitive user forms in process-aware information systems, thereby enhancing the overall user-friendliness of such systems.
Keywords: 330; Intuitive form ordering; Empirical study; User perception